Rational design of a small organic photosensitizer for NIR-I imaging-guided synergistic photodynamic and photothermal therapy. (19th July 2022) - Lv, Shibo; Liu, Yuhan; Zhao, Yanliang; Fan, Xiaoxue; Lv, Fangyuan; Feng, Erting; Liu, Dapeng; Song, Fengling
Abstract : A D–A–D AIEgen TPA-BTZ decorated with long and branched alkyl chains for NIR-I imaging-guided synergistic photodynamic and photothermal therapy is reported. Abstract : Developing a small molecular photosensitizer to achieve multimodal phototherapy has recently garnered attention as a promising strategy for efficient cancer treatment. However, synthesis of a multifunctional small molecular photosensitizer has remained challenging. Here we report an aggregation-induced-emission (AIE)-featured luminogen (AIEgen) TPA-BTZ decorated with long and branched alkyl chains. TPA-BTZ shows long-wavelength emission at ca . 800 nm in the NIR-I region. Moreover, upon laser irradiation, TPA-BTZ could produce O2 ˙ − and 1 O2 via both type I and type II mechanisms for enhanced photodynamic therapy (PDT). The propeller-like structure triphenylamine (TPA) rotators not only endow TPA-BTZ with AIE characteristics but also facilitate heat generation by intramolecular rotation for photothermal therapy (PTT). More importantly, long and branched alkyl chains can create intermolecular spatial isolation in the fabricated TPA-BTZ@PEG2000 nanoparticles (NPs) to allow sufficient intramolecular motion for photothermal conversion. Due to these unique features, in vitro and in vivo evaluations demonstrate that the TPA-BTZ@PEG2000 NPs exhibited long-term NIR-imaging ability, superior tumoricidal activity, and suppressed tumor growth. This research provides new insights for developing new AIEgens for NIR imaging-guided multimodal phototherapy.